Discriminant Validity of the Parent-Proxy Preschool HEAR-QL. Issue 2 (25th October 2021) - Zhang, Amy L.; Jeffe, Donna B.; Lieu, Judith E. C.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The parent-proxy Preschool HEAR-QL (Hearing Environments And Reflections on Quality of Life) is a quality of life (QOL) measure for 2 to 6-year-old children with hearing loss (HL). We compared Preschool HEAR-QL scores for children with HL and children with normal hearing (NH) to examine the measure's discriminant validity. Study Design: Cross-sectional study. Setting: Three tertiary care pediatric otolaryngology clinics. Patients: Two hundred forty-eight parents of children 2 to 6 years old with NH or HL participated. Interventions: None. Main Outcome Measure: The Preschool HEAR-QL has five domains: Behavior and Attention, Hearing Environments, New Social Situations, Social Interactions, and Communications. Scores range from 0 to 100; higher scores indicate higher QOL. Scores for children with NH and with HL were compared using analysis of variance (ANOVA) and area under the receiver operating characteristic (AUROC) curves. Results: Total HEAR-QL mean (SD) scores were higher for children with NH compared to children with HL (75.7 [10.5] vs. 67.5 [15.5], p  < 0.001). Scores were not significantly different between children with unilateral and bilateral HL. Children 2 to 4 years old received lower Communications-domain scores than children 4 to 6 years old across all children (63.7 [25.4] vs. 74.1 [24.3], p  = 0.01) and within the HL cohort (61.3 [25.1] vs. 72.6 [25.3]; p  = 0.009). The Hearing Environments domain displayed excellent discrimination (AUROC = 0.858); other domains showed little to no discrimination. Conclusions: The Hearing Environments-domain of the Preschool HEAR-QL differentiated between children with and without HL. Children with NH had higher scores than children with HL on both Total HEAR-QL and Hearing Environment-domain scores.